Experimental study on mechanical properties and microstructure of cement-based expansion grouting materials for broken coal mass - Feng Zhang; Jinxiao Liu; Jiawei He; Kai Zhang; Zhongcheng Qin (PLoS ONE, 2025)
As the excavation depth of the tunnel increases, the stress on the surrounding rock increases, and the tunnel becomes fragmented, especially in coal tunnels, which require grouting reinforcement. Conventional materials are inadequate for the grouting and reinforcing demands of this type of surrounding rock; therefore, it is essential to create grouting materials with specific expansion properties. First, the orthogonal test method was employed to optimize the expansion grouting materials ratio. Compared with traditional grouting materials, it exhibits certain expansibility along with good fluidity and strength. Based on a comprehensive evaluation of the mechanical properties of the material, the optimal formulation was determined as follows: 10% UEA expansive agent, 5% early-strength agent, and 1.2% water-reducing agent. Additionally, Through SEM tests and grouting reinforcement test of broken coal or rock, it was found that expansive grouting materials can effectively fill micro-fractures in coal rock, enhance the integrity of the surrounding rock, and improve its mechanical properties. The findings indicate that the recovery strength of coal and rock using expansion grouting materials at 7 days is 0.18 and 0.1 greater than that of pure cement; at 28 days, the recovery strength of coal and rock is 0.27 and 0.15 higher than that of pure cement. Ultimately, the expansion grouting materials is employed in engineering applications. Following the application of anchor grouting and expansion grouting materials, the maximum deformation of the roof at the roadway intersection measures 125 mm, while the maximum deformation on both sides reaches 190 mm. The distortion of the surrounding rock of the roadway is well managed. This is essential for the reinforcement of tunnels within shattered surrounding rock and for the secure extraction of coal in mines.